PCOS and Homeopathic Treatment: A Case Study Analysis - Dr Maneesha Soni (The Bioscan, 2024)
PCOS is one of the most prevalent endocrine disorders in females of reproductive age, presenting such symptoms as abnormal menstrual cycles, obesity, hirsutism, and acne. However, conventional treatments alleviate symptoms only, whereas many patients search for alternative methods of treatment that include homeopathy. The present paper develops detailed analyses of ten case stories where homeopathic treatment was applied to alleviate symptoms related to PCOS. Results have shown regularization of the menstrual cycle, reduction in size of cysts, and improvement in allied symptoms like obesity, hirsutism, and acne.